AROMATHERAPY: THE ANCIENT AND MODERN APPROACHTOWARDS DRUG DEVELOPMENT (Baqai Journal of Health Sciences)
Traditional or complementary medicine system is another way of treatment for the healing of medical ailments by natural therapies. Historically the use of aromatherapy is known in the field of clinical sciences by using herbal essential oils in different techniques.Nowadays this field of therapy is used in modern drug development and curing various diseases by essential aromatic oil. The objective of this review is to evaluate the current findings of aromatherapy in the scope of health conditions.